Role of Lipopolysaccharides in the Inflammation and Pyroptosis of Alveolar Epithelial Cells in Acute Lung Injury and Acute Respiratory Distress Syndrome - Shen X; He L; Cai W (Dove Medical Press, 2024)
Xiao Shen,1,* Linglin He,2,* Wanru Cai3 1The Second Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, 310053, People's Republic of China; 2School of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, 310053, People's Republic of China; 3Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, 310005, People's Republic of China*These authors contributed equally to this workCorrespondence: Wanru Cai, Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, 310005, People's Republic of China, Email caiwanru@aliyun.comAbstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) represent a spectrum of common critical respiratory conditions characterized by damage and death of alveolar epithelial cells (AECs). Pyroptosis is a form of programmed cell death with inflammatory characteristics, and activation of pyroptosis markers has been observed in AECs of patients with ALI/ARDS. Lipopolysaccharides (LPS) possess strong pro-inflammatory effects and are a crucial pathological factor leading to ALI in patients and animals. In LPS-induced ALI models, AECs undergo pyroptosis. However, physiologically and pathologically relevant concentrations of LPS lead to minor effects on AEC cell viability and minimal induction of cytokine release in vitro and do not induce classical pyroptosis. Nevertheless, LPS can enter the cytoplasm directly and induce non-classical pyroptosis in AECs when assisted by extracellular vesicles from bacteria, HMGB1, and pathogens. In this review, we have explored the effects of LPS on AECs concerning inflammation, cell viability, and pyroptosis, analyzing key factors that influence LPS actions. Notably, we highlight the intricate response of AECs to LPS within the framework of ALI and ARDS, emphasizing the variable induction of pyroptosis. Despite the minimal effects of LPS on AEC viability and cytokine release in vitro, LPS can induce non-classical pyroptosis under specific conditions, presenting potential pathways for therapeutic intervention. Collectively, understanding these mechanisms is crucial for the development of targeted treatments that mitigate the inflammatory responses in ALI/ARDS, thereby enhancing patient outcomes in these severe respiratory conditions.Keywords: alveolar cell death, inflammatory response, programmed cell death, pathological impact, cytokine activation